What does “Internet” mean to us as we age? A multi-task investigation on the conceptualization of the technological domain across generations - Ilenia Falcinelli; Chiara Fini; Claudia Mazzuca; Guido Alessandri; Fabio Alivernini; Roberto Baiocco; Andrea Chirico; Lorenzo Filosa; Tommaso Palombi; Jessica Pistella; Simone Tavolucci; Fabio Lucidi; et al. (Computers in Human Behavior Reports)
Technological progress is increasing rapidly, and keeping up is particularly challenging for older adults. Thus, adapting technological innovations to human needs has become urgent. The first step toward this aim is to understand how people conceptualize technology. Here, we asked 54 younger and 54 older adults to perform a Go/No-Go, a rating, and a feature generation task to investigate the processing and representation of Technological concepts (e.g., “Internet”) compared to Abstract (e.g., “logic”) and Concrete concepts (e.g., “bottle”). Younger adults showed an elaboration advantage for Technological upon Abstract and Concrete concepts. Technological concepts exhibited a hybrid character, but in older adults, they had a more abstract characterization. Finally, the semantic knowledge associated with Technology was differently organized in content across generations and less structurally robust in older adults. Overall, our results highlight how concepts flexibly change across life and can help societal policies to increase awareness in technology-use across generations.